Policy, Equity and Priority: Ethical Issues of Stem Cell in Developing Countries - B Larijani; F Zahedi (Tehran University of Medical Sciences, 2008)
Ever-increasing advances in the field of bioethics have been encouraged by recent developments of biomedical technolo-gies. Stem cell research and therapy are among the most promising approaches in medicine of which are raised some ethical chal¬lenges. Likewise, the therapeutic potential of stem cell-based therapies created new policy concerns for health care sys¬tems, particularly the issue of equity, priority in resource allocation and justice. There are arguments against and in favor of funding for stem cell research. Governments have also diverse policies in en¬couraging private sector sponsorship to support researches. Iran is one of the pioneers in the field of human embry¬onic stem cell research in the region. The religious de¬crees per¬mitting therapeutic purposes have paved the way for wide-ranging researches. Indeed, the researchers have an obli¬gation to observe moral values. Therefore, the national specific guideline for gamete and embryo research, com¬piled in 2005, is followed in this issue. In this paper, we will discuss the major ethical concerns relating to the issue of equity and justice, and will review the regulatory policies for stem cell research and therapy. On the whole, stem cell research is a global enterprise about which there is a need to think in the context of glob¬alisation and also from the perspective of the developing countries. Stem cell based therapies are expensive and tech¬nologically demanding, the low-resource healthcare systems need to consider a specific national policy and to weigh up costs and benefits to consider making such treatments available. We must ensure that rights, values and wel¬fare of the donor, recipient and the community are respected.